1971
DOI: 10.1080/00288233.1971.10421664
|View full text |Cite
|
Sign up to set email alerts
|

Apple rubbery wood virus

Abstract: Apple rubbery wood virus (RWV) is widespread in apple and pear varieties in New Zealand, having been found in some trees of all varieties examined. Of 278 apple trees tested, 75 percent were infected; and of 43 pear trees indexed, 70 percent carried the virus. The virus has been found to cause symptoms on two New Zealand produced apple varieties, 'Gala' and 'Splendour'. Symptoms on the former are nearly as severe as those on 'Lord Lambourne'; on the latter they are less pronounced, being comparable with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…As well as being infected with green crinkle, both strains had been tested and shown to be infected with the virus or virus-like diseases apple mosaic virus, apple stem pitting virus, apple stem grooving virus, scaly bark, and apple chlorotic leaf spot virus. The apple rubbery wood disease (thought to be caused by a phytoplasma), and which occurs commonly in older apple trees in New Zealand (Chamberlain et al 1971) was not present in either of the green crinkle infection sources. When growth from the buds started in the following season, the buds of the healthy 'Granny Smith' were allowed to develop, while the buds infected with the green crinkle sources were kept restricted.…”
Section: Investigating If Natural Spread Of Green Crinkle Occursmentioning
confidence: 99%
“…As well as being infected with green crinkle, both strains had been tested and shown to be infected with the virus or virus-like diseases apple mosaic virus, apple stem pitting virus, apple stem grooving virus, scaly bark, and apple chlorotic leaf spot virus. The apple rubbery wood disease (thought to be caused by a phytoplasma), and which occurs commonly in older apple trees in New Zealand (Chamberlain et al 1971) was not present in either of the green crinkle infection sources. When growth from the buds started in the following season, the buds of the healthy 'Granny Smith' were allowed to develop, while the buds infected with the green crinkle sources were kept restricted.…”
Section: Investigating If Natural Spread Of Green Crinkle Occursmentioning
confidence: 99%
“…A number of the newer cultivars such as 'Braeburn', 'Freyberg', 'Gala', 'Kidd's Orange Red' and 'Splendour' originated in New Zealand and were found to have as much or more virus and phytoplasma disease infection as overseas cultivars grown in New Zealand. These cultivars could have been infected through the practise of top working them on trees of other apple cultivars, as occurred with some of the early 'Gala' material (Chamberlain et al 1971). However, the apple rootstocks have also come under suspicion as a further source of this infection.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive testing of commercial orchard apple trees in the 1960s and 1970s indicated that there was a high incidence of infection in these trees. Most trees were infected the with virus diseases apple stem pitting, apple stem grooving, apple chlorotic leaf spot, and apple platycapa scaly bark (Wood 1974), and in comparison to other apple growing countries there was a high incidence of apple mosaic virus (Atkinson & Chamberlain 1948), and the phytoplasma disease rubbery wood (Chamberlain et al 1971). Flat limb, at the time thought to be a distinct disease (Atkinson 1971),but now considered to have the same causal agent as rubbery wood (Waterworth & Fridlund 1989), affected all trees of 'Gravenstein' and its red skinned sports, and was latent in a number of other cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier observations had indicated that foliage-affecting viruses were widespread and of high incidence (Chamberlain 1961). Subsequent testing of numerous orchard trees showed that the phytoplasma disease, apple rubbery wood, which was common in New Zealand apple trees, also occurred frequently in pear trees (Chamberlain et al 1971). Further investigations demonstrated the widespread occurrence in pear trees of pear ring pattern mosaic (apple chlorotic leaf spot virus), and pear vein yellows and red mottle virus (Wood 1972).…”
Section: Introductionmentioning
confidence: 99%
“…The earliest investigations into the incidence of virus, phytoplasma and virus-like diseases in commonly grown pear cultivars made use of data obtained from the observation of symptoms in orchard pear trees, and the results of bud inoculation tests with indicator species and cultivars (Atkinson 1948;Chamberlain et al 1971;Wood 1972). For this manuscript, the early data was combined with data obtained by the author from 1957-97'.…”
Section: Virus Phytoplasma and Virus-like Diseases In Commonly Grownmentioning
confidence: 99%